Allometric relationships to assess ontogenetic adaptative changes in three NE Atlantic commercial sea cucumbers (Echinodermata, Holothuroidea) - Silva, F. Azevedo e (2021)
Holothuria arguinensis, Holothuria mammata and Holothuria forskali are three common sea cucumber species found in the NE Atlantic, traded in international markets and susceptible to capture. Allometric relationships reveal if the scaling relationships between biometric characters are proportional with growth, being a useful tool to understand species growth strategies. Allometric relationships of the three species were estimated and compared between them and with populations from different regions. These allometric relationships revealed that the three species have negative allometric growth. However, they have different growth strategies between them and reveal different regional intra-specific growth strategies when compared to other populations, suggesting ontogenetic adaptation as a consequence of external factors.